Learning model development moodle-based problem-based learning to improve critical thinking ability - Poy Saefullah Zevender; Disman Disman; Hari Mulyadi; Edutivia Mardetini; Deni Adriani; Lazuardi Imani Hakam (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Ability thinks critically is ability to make conclusions and judge authenticity as well as truth something based on prior knowledge-owned. Think critically as a complex process that requires cognitive level in process information. In study literature this will discuss development ability and critical participant education with the MOODLE -Based Blended Problem Based Learning Model to support alternative recovery learning during the endemic period of COVID-19. The MOODLE -Based Blended Problem Based Learning Model is considered suitable for develop ability think critical because Blended Problem Based Learning related learning with real world problems as context for participant educate for study think critical and skills solve problem , the MOODLE -based Learning Management System helps participant educate enter into the room digital class and can access materials learning in blended learning as effort restore educational conditions during the COVID-19 endemic. With thereby study this as solution description learning distance far for development ability think critical during the COVID-19 endemic.